1971
DOI: 10.21236/ad0721364
|View full text |Cite
|
Sign up to set email alerts
|

The TEKTITE II Human Behavior Program

Abstract: The habitst provides a relatively stable and constant environment. Unlike many field situations, all subjects could be observed under the same living conditions. This enable* statistical comparison across individuals and across team.3. The design of the habitat provides excellent audio and video coverage. Observers couid monitor almost all in-habitat activity.4. An ertensive battery of psychological data could be obtained on each Aquanaut prior to his miseion--an tmusual situation in field research. 5.The nAtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…The relationship between health and criteria, although nonsignificant, is in a counterintuitive direction and replicates a finding obtained with Scientist-Aquanauts during Project TEKTITE 2 (Helmreich, 1971). This is a tendency for successful performers to have experienced considerable restriction because of illness or accident.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The relationship between health and criteria, although nonsignificant, is in a counterintuitive direction and replicates a finding obtained with Scientist-Aquanauts during Project TEKTITE 2 (Helmreich, 1971). This is a tendency for successful performers to have experienced considerable restriction because of illness or accident.…”
Section: Discussionsupporting
confidence: 79%
“…Birth order was significantly related to the pass-fail criterion with primogeniture associated with success (also replicating the effect found among Aquanauts; Helmreich, 1971).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…NASA has, however, funded a number of analog and simulation studies relevant to spaceflight, some of them quite extensive. These have included research in submersibles such as the Ben Franklin (Seitz et al, 1970), and the Tektite undersea habitat, where aquanauts were systematically observed during a 7-month operational period (Deutsch, 1971;Helmreich, 1971;Nowlis, 1972). Psychological aspects of isolation and confinement have also been examined in volunteer subjects observed in laboratory settings, as in the large projects of Brady and Emurian (1978) and Rogers (Note 2).…”
Section: Psychology's Role In the Pastmentioning
confidence: 99%